Caring for Colorado's forests: an overview of the Colorado State Forest Service - Colorado State Forest Service, author (Colorado State University. Libraries, 2015)
The mission of the Colorado State Forest Service is to achieve stewardship of Colorado's diverse forest environments for the benefit of present and future generations. The Colorado State Forest Service provides technical forestry assistance, wildfire mitigation expertise and outreach and education to help landowners and communities achieve their forest management goals.
Keywords: Colorado forests; Colorado State Forest Service; forest management